Chloroplast genome comparison of Valeriana species with sequence variation, selective pressure, and divergence analysis - Sumin Jeong; Yong-Goo Kim; Yeseul Kim; Bo-Mi Nam; Yun Ji Park; Byung Jun Jin; Inkyu Park (PLoS ONE, 2026)
Valeriana fauriei and V. dageletiana are traditional medicinal plants known for their calming effects and use in alleviating insomnia. However, genomic information for these species is limited. This study aimed to sequence and characterize the complete chloroplast genomes of V. fauriei and V. dageletiana , and to compare them with those of closely related Valeriana species to investigate structural variation, molecular evolution, and divergence history. The chloroplast genomes of V. fauriei , V. dageletiana , and V. jatamansi were highly conserved in overall structure. Minor differences were observed in tandem repeat regions and sequence divergence hotspots, particularly within accD , rps18 , and the trnN–trnL intergenic region. Analysis of 57 protein-coding genes from four species revealed that most genes are under strong purifying selection. However, elevated dN/dS ratios in psbI , rps7 , and rpl23 suggest potential lineage-specific divergence. Phylogenetic reconstruction showed that V. fauriei and V. dageletiana form a clade with V. officinalis , whereas V. jatamansi is an earlier diverging lineage. Divergence time estimation indicated that V. officinalis split from this clade 0.4255 to 1,0839 million years ago, and that V. fauriei and V. dageletiana diverged approximately 0.0205 million years ago. These results provide insights into the evolution of Valeriana chloroplast genomes, highlighting both structural conservation and species-specific variation. The findings contribute to a better understanding of recent speciation events and molecular evolution in this genus, supporting future phylogenomic and taxonomic studies of Valeriana species.